Nonlinear Characterization of Rhodamine 610 dye-doped PMMA Thin Films Under 650 nm CW Laser Light Excitation - Jaffar, Amal F (Al-Nahrain Journal of Science, 2018)
In this work the nonlinear optical properties for Rodamine 610 (R610) in PMMA doped films with different concentrations with the solvent Chloroform by using a high sensitive method known as Z-Scan technique were studied. Z-scan experiment was performed using CW diode laser at 650 nm with the power output of 45 mW, in two parts. The first part was done using a closed-aperture placed in front of the detector to measure the nonlinear refractive index. In the second part; the aperture in front the detector was removed (open aperture) to measure the nonlinear absorption coefficient. The experimental results for closed aperture show that the dye doped films exhibit negative refractive index (self_defocusing) for the films of concentration 10-5and 10- 4 M, while the film of concentration 10-6M exhibits positive refractive index (self-focusing), The results show also that the nonlinear refractive index and the third order nonlinear susceptibility increased with the increasing of the concentration due to the increasing of the film thickness which caused increasing the nonlinear phase shift in the samples. With open aperture z-scan the samples exhibit two photon absorption under the experimental conditions. The effective values of the nonlinear refractive index n2, the nonlinear absorption coefficient β, real and imaginary parts of the third-order optical nonlinearity, χ (3) were evaluated. The results imply that R610 films can be used as a potential medium for various optoelectronic applications including that in optical power limiting.